Torpedo Ink: Vendetta Road - Book 3 - Feehan, Christine (New York : Jove, 2020)
Isaak "Ice" Koval is on a club mission when he sees a woman who stops him dead in his tracks. Soleil looks like an innocent who shouldnt be anywhere near the Torpedo Ink motorcycle club, but Ice will do anything to keep her around.
Keywords: Motorcyclists -- Fiction; Motorcycle clubs -- Fiction; Man-woman relationships -- Fiction; Las Vegas (Nev.) -- Fiction; Romance fiction